2020
DOI: 10.1371/journal.pone.0238620
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamics in stroke thrombolysis (CHiST) study

Abstract: Despite careful patient selection, successful recanalization in intravenous thrombolysis is only achieved in approximately 50% of cases. Understanding changes in cerebral autoregulation during and following successful recanalization in acute ischemic stroke patients who receive intravenous thrombolysis, may inform the management of common physiological perturbations, including blood pressure, in turn reducing the risk of reperfusion injury. Cerebral blood velocity (Transcranial Doppler), blood pressure (Finome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Lidocaine has been included in our country's Essential Drug List and can also be provided in primary hospitals. Therefore, in this study, the concentration of lidocaine continuously pumped by ultrasound-guided SG catheter was chosen to be 0.2% [ 22 ]. The results of this study showed that there was no statistical difference in the incidence of adverse events in patients with continuous pumping of lidocaine under ultrasound-guided SG catheterization compared with the incidence of adverse events in patients treated with conventional SGB.…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine has been included in our country's Essential Drug List and can also be provided in primary hospitals. Therefore, in this study, the concentration of lidocaine continuously pumped by ultrasound-guided SG catheter was chosen to be 0.2% [ 22 ]. The results of this study showed that there was no statistical difference in the incidence of adverse events in patients with continuous pumping of lidocaine under ultrasound-guided SG catheterization compared with the incidence of adverse events in patients treated with conventional SGB.…”
Section: Discussionmentioning
confidence: 99%
“…Since the anterior wall myocardial infarction is mostly the left main coronary artery, compared with the inferior wall myocardial infarction of the right coronary artery disease, its clinical symptoms are more serious, and the treatment time is faster, and the effect is better. Drug thrombolysis is generally effective within 2 hours, and it is not easy to cause complications, so timely thrombolysis is helpful to improve the recanalization rate of infarcted vessels [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the benefits of early intervention with r-tPA on arterial recanalization is wellestablished, the acute effects of thrombolysis on cerebral hemodynamics are less well-categorised. In a small cohort of 11 stroke patients, Lam et al 11 examined the effect of r-tPA infusion on dCA and found during treatment a reduced dCA (phase) within the affected hemisphere in some parameters, while cerebral blood flow velocity (CBFV) remained unchanged. Also noted was a drop in BP immediately before completion of r-tPA infusion, which could have been attributed to factors such as recovery from pain, but does mimic earlier findings in studies investigating streptokinase infusion in patients with myocardial infarction 12 and pulmonary embolism.…”
Section: Fibrinolyticsmentioning
confidence: 99%